Laser Enhanced Hydrogen Passivation of Silicon Wafers. (11th June 2015) - Song, Lihui; Wenham, Alison; Wang, Sisi; Hamer, Phillip; Ahmmed, Mohammad Shakil; Hallam, Brett; Mai, Ly; Abbott, Malcolm; Hawkes, Evatt R.; Chong, CheeMun; Wenham, Stuart
Abstract : The application of lasers to enable advanced hydrogenation processes with charge state control is explored. Localised hydrogenation is realised through the use of lasers to achieve localised illumination and heating of the silicon material and hence spatially control the hydrogenation process. Improvements in minority carrier lifetime are confirmed in the laser hydrogenated regions using photoluminescence (PL) imaging. However with inappropriate laser settings a localised reduction in minority carrier lifetime can result. It is observed that high illumination intensities and rapid cooling are beneficial for achieving improvements in minority carrier lifetimes through laser hydrogenation. The laser hydrogenation process is then applied to finished screen-printed solar cells fabricated on seeded-cast quasi monocrystalline silicon wafers. The passivation of dislocation clusters is observed with clear improvements in quantum efficiency, open circuit voltage, and short circuit current density, leading to an improvement in efficiency of 0.6% absolute.